Efectos de diferentes Densidades de Siembra en el rendimiento de cultivos asociados de Maíz (Zea mays L) con Maní (Arachis hipogaea L) en la estacion experimental agraria "El Porvenir" - Juan Guerra - Corrales Reategui, Juan (2000)
This job was made in order to determiner the best alternative in productivity in association cultivations the corn with peanuts, the variety used was: corn (Marginal 29 tropical) y Peanuts (Blanco Tarapoto), with diferentes densities of seeding (it is indicated in the item 4.3.1.3). Thesis work, was carried out in the land cattle Experimental Station "El Porvenir" located in the Valley of "Bajo Mayo" bolongig to Province and Region san Martin (Perú) it's geographical location is at 16°26' west longitud and 06°34' sout to Green Wich latitud and is at 356 m above sea level. For the execution of work was used land using the completa Randomized Block (BCR), desing with six treatments and Four repetitions, it whose result was Evaluated throu9h Duncan multiple test and variation analysis. The seeding was made in traditional system droping four seed seach hole, to eliminate after 2 plants for each, so much in order to corn for the peanut. The results obtained it statistical analysis it is not show signficative difference among treatment when ajusted of yielding grains of corn. The results obtained in the cultivate of peanut alone and associated, it statistical analysis show significative high diference among treatment when ajusted the grain yielding fluctuate from 641.85 to 315.61 Kg/Ha respectivaly from average of the alone cultivate (T1 alone cultivate) and the associated plants (T3, T4, TS, T6 respectivaly). The best Associated plants result the T6, it has seed ware grown in wat soil it was of 1.00 m x 0.8 m between plant. From the relation benefit/cost ít ware deficit last associative (T4) and obtained positive rentability in the treatment T6, T3, T5 (Asocíatíve) and in the plants testing T1, T2 (maize and Peanut) respectivaly.